Levels of adhesion molecules and clinical outcomes in patients with ischemic stroke after mechanical thrombectomy - Zhang, Xiaohao; Zhou, Feng; Wang, Wei; E, Yan; Chen, Shuaiyu; Cao, Haiming; Lian, Huiwen; Jiang, Teng; Zhang, Yingdong; Shi, Hongchao; Zhou, Junshan (Frontiers in Neurology, 2022)
Background and Purpose: Data on adhesion molecules levels in patients treated with mechanical thrombectomy (MT) is scarce. We aimed to evaluate the association between adhesion molecules levels, symptomatic intracranial hemorrhage (sICH), and clinical outcome and to determine whether the sICH influences the association of adhesion molecules with functional outcome. Methods: Patients with large artery occlusion in the anterior circulation and treated with MT were prospectively recruited. Adhesion molecules including soluble intercellular adhesion molecule-1, soluble vascular cell adhesion molecule-1 (sVCAM-1), and soluble E-selectin (sE-selectin) were tested. An unfavorable outcome was defined as a 90-day modified Rankin Scale score of 3–6. sICH was diagnosed according to the Heidelberg Bleeding Classification within 72 hours of EVT. Results: Of the 310 enrolled patients (mean age, 68.5 years; 198 male), 46 (14.8%) occurred sICH and 173 (55.8%) experienced unfavorable outcome at 90 days. After adjusting for potential confounders, patients with higher sVCAM-1 and sE-selectin levels had an increasing trend of sICH (4th quartile vs. 1st quartile for sVCAM-1; odds ratio [OR], 2.766, P=0.085; sE-selectin; OR, 2.422, P=0.086) and poor outcome (4th quartile vs. 1st quartile for sVCAM-1; OR, 2.614, P=0.025; sE-selectin; OR, 2.325, P=0.046). Furthermore, the sICH might partially mediate the worse functional outcome in patients with higher adhesion molecules levels (Sobel test, P<0.001 for sVCAM-1 and P=0.007 for sE-selectin). Conclusions: There were significant relationships between levels of adhesion molecules and 90-day poor outcome in ischemic stroke patients treated with MT, which was partially mediated by sICH.